HUBUNGAN KONSENTRASI MALONDIALDEHIDA, GLUKOSA DAN TOTAL KOLESTEROL PADA TIKUS PUTIH YANG DIINJEKSI DENGAN STREPTOZOTOCIN - Dhirgo Adji (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2008)
Diabetes mellitus is a major source of morbidity in developed countries. The morbidity and mortality areincreased in patients with diabetes mellitus compared with the general population. Relationship between highsugar or fat consumption with the increasing of glucose or blood cholesterol concentration has been wellunderstood, but the mechanism of diabetes mellitus as a result of streptozotocin injection and its relation withglucose and cholesterol concentration still need to be investigated. So far, many research mention thatstreptozotocin causes only the damage of a cell of pancreas which that directly relates to metabolism of bloodsugar. The purpose of the research is to investigate the mechanism of pancreas damage in its relation with lipidperoxidation. Sixteen male Wistar rats, 200 grams of bodyweight were used as animal models. Rats weredivided into two groups of eight animals each. Group I was not injected with streptozotocin, while Group II isinjected intraperitoneally with streptozotocin 50 mg/kg BW.Three days after the injection, blood samples weretaken intracardially for Malondialdehida (MDA), glucose and total cholesterol analysis. A one-way analysis ofvariance showed that there were significance differences between Group I and II (P